IMPLEMENTASI DATA MINING DALAM MENENTUKAN POLA PEMBELIAN OBAT DENGAN METODE ALGORITMA APRIORI - M. Safii; Alrizca Trydillah (Universitas Methodist Indonesia, 2019)
Data mining is the process to obtain useful information from the warehouse database in the form of science. This study analyzes the data by using data mining algorithms and methods appriori. The system is built is intended for fulfillment in determining the pattern of drug purchases by using Visual Basic 6.0 programming language and MySQL database on a case study in the health sector. The system is built based on the needs of users obtained through interviews and field studies. System development methodology used is the waterfall method which consists Analysis, Design, Coding and Testing. Test results with a priori algorithms and systems built show results that have met the requirements in determining the pattern of drug purchases by the tendency of drug purchases by customers. Compared with the current system performance information is shown on the effectiveness of the system of determining the pattern of drug purchases for the availability of drugs and drug layout for ease in knowing where drugs are viewed from 2 itemset drug.